Life cycle cost analysis of electricity storage facilities in flexible power systems - Nikolaidis, Pavlos; Chatzis, Sotirios P.; Poullikkas, Andreas (My University, 2019)
Global efforts towards de-carbonization have opened the pathway for a test environment of electrical energy storage (EES) topology. In this work, the feasibility of 17 EES facilities applied to 24 individual applications of flexible power networks has been investigated in terms of levelized cost of storage (LCOS) in $/kW. Electricity storage facilities were modelled and evaluated via a life-cycle cost analysis, based on the most realistic EES characteristics and practical applications’ requirements. The results showed that pumped-hydro constitutes the least-cost and most reliable system for large-scale/long-duration applications. Zn-air and vanadium redox (VRB) offer great potential in demand-shifting and reactive support but, due to their wide LCOS range, considerable risk is added in such an investment. Electrochemical double-layer capacitor (EDLC) holds almost the exclusivity in fast-response/frequently-cycled applications, while for medium-term/medium-scale applications and where the large footprint is a prohibitive factor, valve-regulated Pb-acid (VRLA) and hydrogen fuel cells (H2-FC) are more favourable options. However, efficient tools still lack the ability of quantifying all benefits derived from electricity storage, maintaining stakeholders’ concerns for investment. It is apparent that, further research and development implies the decrease of the uncertainty governing the majority of EES technologies, increasing EES implementations and vice versa.
Keywords: EES facilities; Electricity storage; Flexible power networks; Life-cycle cost analysis; Power system operations